Analisis Pelaksanaan Fungsi Pengawasan Inspektorat dalam Penyelenggaraan Pemerintahan Daerah di Kota Baubau - Pahlevi, Ivan; Kadir, Andi Gau; Murfhi, Andi (GOVERNMENT : Jurnal Ilmu Pemerintahan, 2012)
Abstract: This study aims to determine the effectiveness of the oversight function performed as a local government watchdog and what influences oversight function performed by the Inspectorate of Baubau. This research was conducted in the City Baubau, with informants inspectorate employees who are considered competent. Pengumulan data is done through field observations and in-depth interviews. This research method is descriptive qualitative. The effectiveness of the oversight function performed by the State Inspectorate Baubau three namely: First, the preparation of the monitoring conducted by the inspectorate officials authors assume that what was done by the inspectorate officials have been quite effective in accordance with standard operating procedures that apply every year. Second, the implementation of the monitoring conducted by the inspectorate officials authors assume that what was done by the inspectorate officials have not been effective. Third, the effectiveness of the accountability report on the preparation and supervision of each SKPDs been checked yet supported by the availability of accurate data / valid in order to be served. Factors affecting the implementation of supervisory functions of the inspectorate in the regional administration in the City Baubau are: (1) Internal factors and (2) External Factors.Keywords: Function, monitoring, inspectorate Abstrak: Penelitian ini bertujuan untuk mengetahui efektifitas fungsi pengawasan yang dilakukan sebagai pengawas pemerintahan daerah dan apa yang mempengaruhi fungsinya pengawasan yang dilakukan oleh Inspektorat Kota Baubau. Penelitian ini dilakukan di Kota Baubau, dengan informan pegawai inspektorat yang dianggap memiliki kompetensi. Metode penelitian ini adalah deskriptif kualitatif. Adapun efektifitas pelaksanaan fungsi pengawasan yang dilakukan oleh Inspektorat Kota Baubau ada tiga yakni : Pertama, penyusunan pengawasan yang dilakukan oleh pejabat inspektorat penulis menganggap bahwa apa yang dilakukan oleh pejabat inspektorat sudah cukup efektif sesuai dengan SOP yang diberlakukan disetiap tahunnya. Kedua, pelaksanaan pengawasan yang dilakukan oleh pejabat inspektorat penulis menganggap bahwa apa yang dilakukan oleh pejabat inspektorat belum efektif. Ketiga, efektivitas pelaksanaan penyusunan dan pertanggungjawaban laporan hasil pengawasan dari masing-masing SKPD yang sudah diperiksa belum ditunjang oleh ketersediaan data yang akurat/valid guna dapat disajikan. Faktor-faktor yang mempengaruhi pelaksanaan fungsi pengawasan inspektorat dalam penyelenggaraan pemerintahan daerah di Kota Baubau adalah : (1) Faktor internal dan (2) Faktor Eksternal.Kata kunci: Fungsi, pengawasan, inspektorat